STRUKTUR, PERILAKU, DAN KINERJA USAHA PENGGEMUKAN SAPI POTONG DI DESA BICORONG KECAMATAN PAKONG KABUPATEN PAMEKASAN - Intan Nia Tata Ayu; Andrie Kisroh Sunyigono; Elys Fauziyah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Pamekasan Regency is the center for Madura cattle development in East Java. The basic problem faced by farmers is that they are not free to sell livestock and their bargaining position is weak in determining prices. The purpose of this study was to analysis the structure, conduct and performance of beef cattle fattening business in Bicorong Village, Pakong District, Pamekasan Regency. The sample of this study consisted of 42 farmers and 13 respondents from marketing institutions using snowball sampling. The data analysis method used the SCP approach. The results show that the market structure in marketing beef cattle in Bicorong Village leads to an oligopoly competitive market with moderate concentration. The market conduct shows the price of beef cattle is determined by trader. For performance, it’s efficient because there is only one marketing agency involved and the share received by farmers is quite large, namely ≥ 60  percent.